Vitrification and Nanowarming of Kidneys. Issue 19 (11th August 2021) - Sharma, Anirudh; Rao, Joseph Sushil; Han, Zonghu; Gangwar, Lakshya; Namsrai, Baterdene; Gao, Zhe; Ring, Hattie L.; Magnuson, Elliott; Etheridge, Michael; Wowk, Brian; Fahy, Gregory M.; Garwood, Michael; et al.
Abstract: Vitrification can dramatically increase the storage of viable biomaterials in the cryogenic state for years. Unfortunately, vitrified systems ≥3 mL like large tissues and organs, cannot currently be rewarmed sufficiently rapidly or uniformly by convective approaches to avoid ice crystallization or cracking failures. A new volumetric rewarming technology entitled "nanowarming" addresses this problem by using radiofrequency excited iron oxide nanoparticles to rewarm vitrified systems rapidly and uniformly. Here, for the first time, successful recovery of a rat kidney from the vitrified state using nanowarming, is shown. First, kidneys are perfused via the renal artery with a cryoprotective cocktail (CPA) and silica‐coated iron oxide nanoparticles (sIONPs). After cooling at −40 °C min −1 in a controlled rate freezer, microcomputed tomography (µCT) imaging is used to verify the distribution of the sIONPs and the vitrified state of the kidneys. By applying a radiofrequency field to excite the distributed sIONPs, the vitrified kidneys are nanowarmed at a mean rate of 63.7 °C min −1 . Experiments and modeling show the avoidance of both ice crystallization and cracking during these processes. Histology and confocal imaging show that nanowarmed kidneys are dramatically better than convective rewarming controls. This work suggests that kidney nanowarming holds tremendous promise for transplantation. Abstract : Vitrification dramatically increases organ storage times in the cryogenic state beyond current storage limits. However, vitrified kidneys cannot currently be rewarmed sufficiently rapidly or uniformly to avoid ice crystallization or cracking failures. A new radiofrequency rewarming technology called "nanowarming" addresses this problem by exciting magnetic nanoparticles to rewarm vitrified kidneys rapidly and uniformly.